Teatro de bonecos como ferramenta de sensibilização ambiental em unidades de conservação - Câmara, Vanessa Oliveira Fernandes (2016)
The current situation of the planet involves several discussions about the loss of biological diversity. Brazil, one of the largest biodiversity, could not avoid such discussions, declare it as essential to ensure human survival and the maintenance of ecological balance. Marine ecosystems are already recognized for their ecosystem services and genetic diversity that is home. However, the threats that surround it is worrying governments and society. The introduction of legally protected areas has become a conservation strategy widely used around the world. In this context, it was established the Marine State Park Areia Vermelha (PEMAV) in order to maintain a reef environment of extreme biological importance for the state of Paraiba. The PEMAV, a conservation unit (UC) for full protection, is in the area of direct influence of the estuary of the River Paraiba, nursery several marine species. Thus, the park has been the subject of studies and concerns, both from the point of view of environmental risk factors generating, as to how the human being is related, perceives and behaves opposite the conservation process. It is in this scenario that is inserted discussion around UC management tools. This study is thematic focus environmental awareness coupled with the non-formal environmental education contextualized with the weaknesses of the study area and applied in a playful manner, through the puppet theater. Thus, the study aimed to evaluate the puppet theater as an educational tool focused on environmental awareness in protected areas and to draw the perception of children's play and public PEMAV visitors with the joy of the dolls. To achieve these objectives bibliographical research was realized, document analysis and development tool based on the practices of Environmental Perception, through a questionnaire applied to the involved Bantam public. The data were analyzed by content analysis (CA) and triangulation of data. Thus, based on the interpretation of environmental perception and behavioral analysis, the results revealed positive aspects of the use of playful tool at UC and indicated aspects that need more attention to the use of puppetry in protected areas open to the public. In this context, some recommendations are immersed in the final text of this work.